2015
DOI: 10.1186/s13104-015-1369-4
|View full text |Cite
|
Sign up to set email alerts
|

Teaching referral skills to medical students

Abstract: BackgroundReferrals are an important and frequent part of a junior doctor’s work. Difficulty with making successful referrals is also very common. Despite this, training in referral skills is not routinely carried out in medical schools.ResultsWe designed and delivered a 1-h interactive lecture to final year medical students to teach referral skills. The lecture was delivered on six occasions to up to 70 students at each session. 191 students attended and provided evaluation. 68 % of students had no previous t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…EWS is cited by clinical staff as a way to facilitate deterioration communication and package information, but care delays because of poor communication remain significant . Referral is high risk, with significant errors likely to occur and failures being directly attributable to incomplete information . In recognition of this problem, tools have been developed to improve communication during referral, such as Situation, Background, Assessment, and Recommendation (SBAR)…”
Section: Introductionmentioning
confidence: 99%
“…EWS is cited by clinical staff as a way to facilitate deterioration communication and package information, but care delays because of poor communication remain significant . Referral is high risk, with significant errors likely to occur and failures being directly attributable to incomplete information . In recognition of this problem, tools have been developed to improve communication during referral, such as Situation, Background, Assessment, and Recommendation (SBAR)…”
Section: Introductionmentioning
confidence: 99%
“…Its main cause is to reduce the overload on hospitals. Nevertheless, many hospital consultation clinics are still overloaded with patients who could reach there without a referral (16).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 A survey among final year medical students revealed that two-thirds of the participating final year medical students had received no previous training in referral skills and recommended the inclusion of training in referral skills to their curriculum. 5 Therefore, it is recommended that EM residents should be formally imparted instruction on telephone consultation skills related to inpatient specialties. 5,6 Learner-centred experiential sessions that necessitate the active engagement of resident physicians constitute the most effective approaches in teaching communication skills and can lead to behavioural changes.…”
Section: Introductionmentioning
confidence: 99%
“…5 Therefore, it is recommended that EM residents should be formally imparted instruction on telephone consultation skills related to inpatient specialties. 5,6 Learner-centred experiential sessions that necessitate the active engagement of resident physicians constitute the most effective approaches in teaching communication skills and can lead to behavioural changes. 7 A one-to-one experiential session involves direct observation of a learner's telephone referral experience by an experienced EP, followed by appropriate and timely feedback and discussion.…”
Section: Introductionmentioning
confidence: 99%